Signature of Y-forking in ionogram traces observed at low-mid latitude Indian station, New Delhi, during the earthquake events of 2020: ionosonde observations - Bhardwaj, Arti; Gupta, Ankit; Ahmed, Qadeer; Singh, Anshul; Gupta, Sumedha; Sarkhel, S.; Sunil Krishna, M. V.; Pallamraju, Duggirala; Pant, Tarun; Upadhayaya, A. K. (Frontiers in Astronomy and Space Sciences, 2023)
We have examined ionospheric response to eleven earthquake events measuring less than four on the Richter scale during the year 2020 that occurred in the vicinity of New Delhi (28.6°N, 77.2°E, 42.4°N dip). Perceptible ionospheric perturbations two to nine days prior to these earthquake events resulting in more than 250% variation in electron density are observed. We found distortion of ionogram trace in the form of Y forking majorly at New Delhi on the precursor day and after the earthquake event. Traces of Y forked ionograms were also observed at Ahmedabad (23°N, 72°E, 15°N dip) and Trivandrum (8.5°N, 76.9°E, 0.5°N dip). These Y-forked ionograms are one of the first observations from Indian latitude and are looked at as a signature of Travelling Ionospheric Disturbances (TIDs).